Clean pyrolysis oil from a continuous two-stage pyrolysis of scrap tires using in-situ and ex-situ desulfurization. (15th December 2017) - Choi, Gyung-Goo; Oh, Seung-Jin; Kim, Joo-Sik
Abstract: Scrap tire pyrolysis was conducted to produce low sulfur oil (below 0.45 wt%), which is strongly demanded for reduction of SOx emissions. In the experiments, a continuous two-stage pyrolyzer consisting of an auger reactor and fluidized bed reactor and various additives (CaO, Fe, FeO, calcined olivine) and fluidizing media (product gas and N2 ) were tested for the in-situ desulfurization. The auger reactor operated at ∼340 °C yielded a liquid with 3–5 wt.% of pyrolysis oil. The content of DL-limonene in this liquid product was ∼51 wt% and increased further to ∼76 wt% through subsequent ethanol extraction. The fluidized bed reactor (∼510 °C) produced pyrolysis oils with yields around 30–37 wt%. N2 reduced the sulfur content in pyrolysis oil more effective than product gas, due to its dilution effect. The majority of tested desulfurizing additives reduced the sulfur content in pyrolysis oil, and the application of FeO powder and N2 in particular produced pyrolysis oil with the lowest sulfur content (0.39 wt%). Two ex-situ desulfurization methods (ethanol extraction and oxidation/ethanol extraction) were tested to further reduce the sulfur content. The oxidation/ethanol extraction method decreased the content of sulfur in pyrolysis oil to 0.17 wt%. Highlights: Scrap tires were successfully pyrolyzed in a continuous two-stage pyrolyzer. The oil from the auger reactor was enriched with DL-limonene. Pyrolysis oil yields from the fluidized bed reactor were 36–44 wt%. The sulfur content of in-situ desulfurized pyrolysis oil was 0.39 wt%. The sulfur content of ex-situ desulfurized pyrolysis oil was 0.17 wt%.